Creating An E-Module For A Basic Musical Instrument (Compulsory Piano Course) - Ramafisela, Lingga (Jurnal Seni Musik, 2021)
Learning basic instruments (compulsory piano) is a basic piano practice course that must be taken for all students except for piano major students. Learning this basic instrument (compulsory piano) encountered obstacles, namely that students still did not understand and could play the piano. This is certainly an obstacle in the process of learning basic instruments (compulsory piano) especially in the current situation where learning is carried out online. Electronic modules or e-modules are needed to assist students in an effective and efficient learning process. This basic instrument e-module design (compulsory piano) can function as a problem-solving idea, namely to develop effective and efficient learning materials. The purpose of this study is to facilitate the learning process in the basic instrument class (compulsory piano). The basic instrument e-module design (compulsory piano) is an important element in online learning which is arranged in a systematic and interesting way. This electronic module can be accessed using gadgets owned by students and supports the environmentally friendly (paperless) movement. The research method used is Research and Development with several stages, namely need assessment, design, and development/implementation. The last stage in this research is evaluation and drawing conclusions. The data are directly obtained in the basic instrument class (compulsory piano) in the Music Education Study Program. This e-module design is expected to be useful for the effective and efficient progress of the learning process for basic instruments (compulsory piano) in the Music Education Study Program, FSP ISI Yogyakarta.